Isolation and Characterization of Bacillus Strains from Egyptian Mangroves: Exploring Their Endophytic Potential in Maize for Biological Control of Spodoptera frugiperda - Hayam M. Fathy; Mona Awad; Nawal A. Alfuhaid; El-Desoky S. Ibrahim; Moataz A. M. Moustafa; Ayatollah S. El-Zayat (Biology)
The widespread use of pesticides to manage Spodoptera frugiperda has led to significant challenges. This insect has developed resistance to 47 active insecticide ingredients. Therefore, endophytic entomopathogenic bacteria have been explored as an alternative pest management strategy, offering the potential to reduce reliance on chemical pesticides. The current study aims to evaluate the colonization potential of indigenous marine Bacillus strains as endophytes in maize plants and to assess their insecticidal activity against S. frugiperda. Four inoculation methods—foliar application, seed treatment, soil drenching, and a combination of all three—were used to establish the Bacillus strains as endophytes in maize plants. Our results showed that the promising native Bacillus strains exhibited both antibacterial and insecticidal effects against S. frugiperda neonates under laboratory conditions. Foliar application of Bacillus sp. Esh39 caused the highest mortality rate (65%), followed by Bacillus tequilensis R39 (60%). However, this method did not significantly enhance plant height or chlorophyll content. The potential of these native Bacillus strains warrants further investigation to improve biological control via endophytic mediation. Our findings provide valuable insights into the bacterial diversity and functionality of mangrove ecosystems and pave the way for innovative, sustainable insect management strategies.